RETRACTED : The Effect of Marketing Mix on NMAX Motorcycle Sales Volume at Yamaha Putera Agung Dealership, South Jakarta - Muhammad Rifqi Akmal; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
The study aims to determine the effect of price, product, distribution and promotion on the sales volume of NMax motorcycles at Yamaha Putera Agung dealers in South Jakarta. With product and promotion variables it is assumed not to affect the sales volume variable. In this study, the price variable uses a proxy for down payment and installment period, while for the distribution variable uses a proxy for the amount of leasing. This research uses a qualitative approach. The type of data in this study is secondary data using time series data. The population in this study is unknown by taking 1 (one) research sample. The analysis method used in this study is a multiple linear regression analysis method processed by SPSS 24.0 software. The results of this study show that down payments and installment periods which are proxies of prices negatively affect sales volume, while the amount of leasing which is a proxy of distribution has a positive effect on sales volume.